Improvement in the quality of teaching in physical education by use of multimedia technology and mobile phones - Liang, Y.; Gao, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: One of the main approaches in physical education (PE) is direct teaching, so the use of multimedia in PE is common. However, in practice, teaching with multimedia is not efficient because of limitations in access to appropriate equipment. Most classes only have the use of one camera, which results in a lack of teaching quality since athletic skills cannot be viewed from multiple angles. With the development of high-tech mobile phones, many students nowhave access to blue tooth and camera technologies. The interaction between students and teachers and the quality of teaching may be improved by taking advantage of this portable equipment. This paper suggests that physical education teaching quality can be improved and the motivations of students can be inspired by using the resource of students` cell phones. Methods Based on literature, investigation, interview, and experiment, the authors implemented a comparative research design on 40 Volleyball students from two PE classes at Guangzhou University of Sport. Class 1 was the experimental class and the Class 2 was the control class. All students in both classes had the same foundation background in volleyball and the same teacher taught both classes. One camera was used in the control as the multimedia equipment. Besides this camera, students` from Class 1 used their camera-enabled cell phones as multimedia equipment. After a semester, the teacher compared the effectiveness between the two classes by evaluating students` skills and the ratio of success. Results All students had mobile phones, 98 percent of these phones had cameras or blue tooth functions. Students in class 1 performed better than the control group. Class 1 students analyzed the teachers` demonstrations by the video they made with their cell phones. In addition, they tested their own acts and their partners` acts. This improved their sense of cooperation, as well as their ability for selfmodification. Students in class 1 mastered the video techniques rapidly. This was demonstrated by less clumsiness in grasping the volleyball skills, and by skillfully mastering the volleyball techniques in a shorter amount of time. Test results for the students` skills in class 1 were improved compared to those in the control group. Conclusions The use of mobile phones among physical education students provided a feasible approach to enhance their skill development and other teaching outcomes. The effectiveness of students` studies improved together with enhanced motivation for learning. Positive attitudes to study were combined to promote the achievement of teaching goals using mobile phones as a component of multimedia teaching.